Słowacka literatura współczesna w polskim horyzoncie odbioru w 2016 roku - Buczek, Marta (Przekłady Literatur Słowiańskich, 2017)
Slovak Contemporary Literature in the Polish Horizon of Reception in the Year 2016 The author of the paper characterizes Slovak literature translated into Polish in 2016. She analyzes in detail the translations of Slovak prose Piata loď by Monika Kompaníkova (in the Polish version Piąta łódź), Informácia by Maroš Krajňák (Informacja) and Zu by Silvster Lavrík (Zu). She also interprets Polish translations of Slovak prose in anthologies Portrety z bliska and Tu i teraz, which include the prose of Radovan Brenkus, Ľudovít Petraško, Peter Karpinský, Martin Vlado and women writers from the associations Aspekt and Femina, among others, Mária Bátorová, Jana Bodnárová, Etela Farkašová, Jana Juráňová, Helena Dvořáková, Rúth Lichnerová, Eva Maliti Fraňová. The author of the paper is interested in reception of Slovak contemporary literature in the secondary horizon. Keywords: Slovak Literature in Polish Translations, Literary Translation, Monika Kompaníková, Maroš Krajňak, Silvester Lavrík, Radovan Brenkus, Association of Women Writters Aspekt, Club Femina